Does the number of incisions in video-assisted thoracoscopic surgery matter? - Hansen, Henrik Jessen; Varela, Gonzalo; Petersen, René Horsleben; Walker, William S. (Journal of Thoracic Disease, 2016)
The main goal for any doctor should be to give the patients the best possible treatment for their medical condition, whatever it is. The decision regarding treatment should be based on scientific evidence, ideally via clinical trials. This can often be quite straight forward in pharmaceutical medicine, where you can design randomized and double blinded studies in order to identify evidence for the superior treatment. In surgery, however, the preferred technique quite often is more eminence than evidence based. It is difficult to design adequately large studies and very difficult to do so in a double blinded fashion. Senior peer pressure and difficulty with constructing effective clinical surgical trials (often interlinked phenomena) leads to conservatism and resistance to radical new ideas.